Canalicular repair in an infant with a simple modification in implantation technique of a conventional innovative implant for canalicular stenting - Vikas Sharma; Ritesh Waghray; Anuradha Singh; Agrima Bhatia; Akanksha Sahu; Nidhi Kalra; Subhasish Patnaik (Oman Journal of Ophthalmology, 2025)
Eyelid injuries associated with canalicular rupture may lead to lacrimal drainage obstruction if not repaired in time. Of the various techniques available, monocanalicular stenting is the procedure of choice. However, these stents are not only costly but also their availability is a limitation. Majority literature focuses on innovative techniques to identify the lost medial part of canaliculi. We developed a novel surgical technique for canalicular repair by inserting a 26 gauge plastic sleeve of pediatric Intravenous cannula utilizing 27 gauge metal irrigation cannula as a guiding tool.